An electrochemical study of the crevice corrosion of titanium - Pariona,M.M. (1997)
The influence of different parameters (pH and aeration of the solutions, temperature and geometric features) on the electrochemical behavior of commercially pure titanium in sodium chloride solutions at intermediate temperatures was studied, with the aim of contributing to the understanding of the crevice corrosion susceptibility of this metal. The titanium ion that forms in the active dissolution region was determined bo be Ti3+. Electrochemical and gravimetric techniques were used. Pitting of titanium was found only at high anodic overpotentials (~5.3V), but crevice corrosion can occur at the free corrosion potential. The utilization of a two-compartment cell showed that a maximum ratio of cathodic area to anodic area cannot be surpassed in order to model the activation of the metallic surface in the crevice. The development of an ohmic drop through the corrosion products at the entrance of the crevice is proposed as a stabilizing factor in the corrosion process.